2020
DOI: 10.1021/acsanm.9b02089
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Nanoparticles and Rifampicin Synergistically Damage the Membrane of Mycobacteria

Abstract: The emergence of drug resistance in tuberculosis requires alternative strategies to combat the resistance. To this end, we have synthesized zinc oxide nanoparticles (ZnO NPs) of 11 nm diameter and evaluated its effect against mycobacteria alone, as well as in combination with the first-line anti-TB drug, rifampicin. These ZnO NPs themselves are not inhibitory against the wild-type (WT) Mycobacterium smegmatis, up to a concentration as high as 256 μg/mL. However, a subinhibitory concentration of only 32 μg/mL o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
0
4
0
3
Order By: Relevance
“…Mistry et al [ 318 ] studied the synergistic action of ZnO NPs and RIF against Mycobacteriym smegmatis , a non-virulent strain like MTB. The ZnO NPs were synthesized through precipitation in organic media, using zinc acetate dihydrate and sodium hydroxide in methanol.…”
Section: Nanoscale Drug Delivery Systemsmentioning
confidence: 99%
“…Mistry et al [ 318 ] studied the synergistic action of ZnO NPs and RIF against Mycobacteriym smegmatis , a non-virulent strain like MTB. The ZnO NPs were synthesized through precipitation in organic media, using zinc acetate dihydrate and sodium hydroxide in methanol.…”
Section: Nanoscale Drug Delivery Systemsmentioning
confidence: 99%
“…coli) confirmed that hybrid PDA@ZnO NPs on the functionalized surface provided an effective antibacterial effect by means of three potential pathways: (a) ROS damage the intracellular contents, including proteins, DNA, ATP, etc., through intense oxidative stress reactions after being internalized into the bacterial cell membrane; (b) zinc ions released from the ZnO nanoparticles can cause mechanical damage to the bacterial cell wall, thus penetrating cell membranes to inhibit active transport and glucose metabolism and disrupt metal ion homeostasis and enzyme systems when the concentration reaches a specific level; (c) ZnO nanoparticles directly contact bacterial cell walls, causing damage to the membrane integrity and subsequent death . Interestingly, ZnO NPs were coupled with antibiotics to exhibit synergistic efficacy and support the antibiotic resistance fight. Finally, antibacterial ZnO NP-based materials were widely proposed for water purification, acting as both photocatalysts and antibacterial agents. ,,, …”
Section: Antimicrobial Applicationsmentioning
confidence: 99%
“…For instance, INH-loaded selenium NPs favor Mtb localization within lysosomes [ 112 ]. Similarly, RFP-loaded ZnO NPs cause irreversible damage to the membrane of Mycobacterium smegmatis (a surrogate of Mtb ) and are also effective against resistant strains of Mycobacterium bovis [ 132 ].…”
Section: The Potential Of Nanoparticles Regarding the Treatment Of Tu...mentioning
confidence: 99%